Above and beyond the content: Feelings influence mental simulations. (19th June 2020) - Mrkva, Kellen; Cian, Luca; Van Boven, Leaf
Abstract: Gilead et al. present a rich account of abstraction. Though the account describes several elements which influence mental representation, it is worth also delineating how feelings, such as fluency and emotion, influence mental simulation. Additionally, though past experience can sometimes make simulations more accurate and worthwhile (as Gilead et al. suggest), many systematic prediction errors persist despite substantial experience.